EVALUASI MUTU SUSU FERMENTASI BIJI NANGKA DENGAN VARIASI SUSU SKIM MENGGUNAKAN BAKTERI Lactobacillus casei subsp. casei R-68 - Ardi, Febrian; Pato, Usman; Rossi, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Jackfruit seeds and skim milk fermented by Lactobacillus casei subsp. casei R-68 expected to produce fermented milk that has more complete nutritional value and health benefits. Lactobacillus casei subsp. casei R-68 was isolated from dadih, a type of fermented milk in West Sumatra, Indonesia. This study used Completely Randomized Design experiment with 6 treatments and 3 replications to obtain 18 experimental units. The data obtained were statistically analyzed using Analysis of Variance (ANOVA). If F count is greater than or equal to F table then it continued with DNMRT test at 5% level. The results showed that pH of jackfruit seed fermented milk were 4,83-5,80, total lactic acid 0,52-1,17%, total solids 10.15-25.40%, protein content 23.76-6.16% and ash content 0.08-1.07% after fermentation.While descriptive assessment of which felt a bit acidic, yellowish white to white and its viscosity was dilute to thick and favored by panelists.Keywords: Jackfruit seeds, Lactobacillus casei subsp. casei R-68 and skim milk.